(3JHUQI GdeHJOj aj GdgjFIs - (3GdLGeYj, GdYGedj, GdMGQKj GdgePGfj, fhQ GdOjf, Ydj Hf GdMSjf Hf eMjj GdOjf GHf YHO GddWja Hf Ydj, J (B1135(3g`s ((3HNW GdeDdas)
(3ChdgG (B:s
(3GdMeO ddg GdPj HdG eOO(B***(3bO QaY GdSeGA ef ZjQ YeOs
(3BNQgG (B:s
(3hNjQ UdGI Gddg JZTi eMeOG(B***(3hYJQJg PNQj hjG MHPG GdPNQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: (3L(B4(3, U(B281s
(3GdCYdGe(B: (3L(B4(3, U(B281s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3Gdadc hGdJfLje hGdejbGJs